Exchange traded commodities as a category of innovative products on European financial markets - Adam Marszk (e-Finanse: Financial Internet Quarterly, 2017)
The article presents the main features of one category of innovative financial products - exchange traded commodities (ETCs) and results of the analysis of the European market for ETCs. ETCs are products listed and traded on the stock exchanges and they offer investors returns based on various assets (commodities or currencies). In contrast with the most widely recognized exchange traded funds (ETFs), ETCs are structured as debt instruments due to legal requirements regarding investment funds in the European Union. The European ETCs market is the largest in the world (in terms of assets its share in the global market in 2015 was close to 98%). It had developed rapidly until 2012 when total assets reached the record-high value of ca. 26,6 billion EUR (i.e. 9,5% of total assets of all exchange traded products listed in Europe). Over the next few years both the value of assets and market share of ETCs decreased significantly, mostly due to decline of the tracked assets' prices (especially commodities) - during the analyzed time periodthe average flows to commodity or currency ETCs were close to 0. An important feature of the European market is its high concentration level, both in terms of companies launching ETCs and locations of the trade in the share of ETCs. Four ETC providers manage most of the assets (with the cumulated market share of over 94%). Three exchanges -in London, Milan and Frankfurt am Main account for almost the entire regulated market turnover of ETCs in Europe.
Keywords: G23; G11; Q02; 330; exchange traded commodities; exchange traded funds; commodities; currency; asset management